Non-specialist English teachers' pedagogical content knowledge in teaching English at tahfiz schools / Zarith Sofia Zaid ... [et al.] - Zaid, Zarith Sofia; Damio, Siti Maftuhah; Mat Rahim, Nur Hazura (Universiti Teknologi MARA, Kedah, 2021)
Tahfiz schools are gaining popularity overtime. Thus, serious attention needs to be given to the overall systems in Tahfiz schools, especially the academic subjects and matters related to it. This is the focus of this study-the English teachers at Tahfiz schools who are normally non-specialist English teachers (NSETs), or teachers with no formal qualification to teach. Hence, this research aims to investigate the levels of the NSETs' Pedagogical Content Knowledge (PCK). In determining the level of the NSETs' PCK, both theories of constructivist and Bandura are taken into consideration. This means, if the NSETs have a strong self-efficacy, which may arise from their experience, the unawareness of the NSETs might drive them to see PCK as unchallenging. An explanatory mixed-method was utilized with 34 NSETs obtained through snowball sampling. The findings revealed the NSETs have an intermediate level of PCK. It is important for the NSETs to have a series of pedagogical courses, that will broaden their knowledge in teaching English subject. Besides, a mentoring program with specialist English teachers from neighbouring government schools, seems beneficial to ensure that the NSETs will be at par in terms of knowledge and experience to the current education system.